Understanding the role of communication and mediation strategies in community-led territorial innovation: a systematic review - Silva, Paula Alexandra; Tymoshchuk, Oksana; Reno, Denis [UNESP]; Almeida, Ana Margarida; Pedro, Luis; Ramos, Fernando (Interaction Design & Architectures, 2020)
This article brings together empirical academic research on community-led territorial innovation initiatives. By engaging in a systematic literature review, the research analyses the role of digital technology in supporting community-led initiatives. Besides identifying the technologies used, this research develops an understanding both on its purpose of use and on its relation to communication and mediation strategies. A clear gap is found not only in terms of research reporting on community-led initiatives, but also on research studying the specific use of digital technology by those communities, highlighting a need for future research in the area. From an initial set of 1312, six articles are identified which meet the inclusion criteria for this review and only five of them report on technology use. Results show that a diversity of digital technologies, from blogs to online repositories, is used by the initiatives analysed, leveraging on the global coverage of the Internet. Besides a key role in supporting community collaboration and cooperation, digital technology also emerges as an important vehicle for community debate and as an enabler of community empowerment and advocacy.
Keywords: Territorial innovation; Community-led initiative; Digital Technologies; Digital Media; Communication; Mediation